Optimizing performance and mood state in competitive swimmers through tapering strategies - Aouani, Hajer; Amara, Sofiene; Rebai, Haithem; Barbosa, Tiago M.; van den Tillaar, Roland (Frontiers in Psychology, 2024)
Tapering is a concept that is of great importance in relation to performance, due of its great effect on the psychological and physical condition of the swimmer. Therefore, the present study aims to investigate the effect of two-week of tapering characterized by a progressive training volume reduction on mood state and swimming performance in competitive swimmers. Twenty-four competitive male swimmers were randomly assigned into two groups. Experimental group (age = 2 This is a provisional file, not the final typeset article 16.9 ± 0.5 years) and control group (16.1 ± 0.4 years). The mood subscales (tension, depression, anger, fatigue, confusion and vigor), total mood disturbance and swimming performance (50-m front crawl) were measured in pre and posttest. Our findings revealed a significant improvement in mood subscales (20.8% to 47.8%), total mood disturbance (14.4%) and in swimming performance (3.5%) after two weeks of tapering training. A significant correlation was observed between the total mood disturbance and the 50 m front crawl (r = -0.63) only in the experimental group. It was concluded that a progressive reduction in training volume with a maintain of intensity could improve mood state and swimming performance. In addition, a change in total mood disturbance could affect swimming performance. Swimming coaches are advised to include tapering period according to the standards we mentioned earlier before competitive swimming to improve mental state, which helps the swimmers to overcome the negative influences of overtraining and therefore they can promote sprintswimming performance.